Climate seasonality and plant vigor effects on reproductive phenology of Potalia turbinata (Gentianaceae) in Costa Rica - Salazar, Rachel (2025)
Introduction: Potalia turbinata (Gentianaceae) is a treelet distributed from Nicaragua to Panama. Information on its reproductive biology and phenology is lacking. Objective: To describe the reproductive phenology of P. turbinata, morphologically characterize its fruits and seeds, and determine whether flower and fruit production correlates with climate (temperature and precipitation) and plant vigor. Methods: The research took place at Tirimbina Biological Reserve in Costa Rica, January 2017–March 2019. Monthly counts of flowers and fruits were conducted on 86 plants. We used circular statistics to determine the duration and peak of flowering and fruiting. Fruit production was compared between years to describe reproductive cycles. We correlated flower and fruit abundance with climatic conditions. Plant measurements included height, basal stem diameter, leaf crop, seeds per fruit, fruit and seed dimensions, and fruit hardness. We used height, diameter, and number of leaves as proxies for plant vigor and compared plant vigor between fruiting (i.e., number of fruits) and non-fruiting plants. Results: Flowering lasted 2–6 months per plant, peaking in April, while fruiting was prolonged (3–10 months), moderately peaking in August. Flower abundance was negatively correlated with precipitation, but fruiting showed no significant correlation with climate. Fruit production negatively correlated with plant height and positively correlated with basal stem diameter. Non-fruiting plants had more leaves than fruiting plants. Conclusions: At the population level, P. turbinata flowered and fruited annually. Individuals were supra-annual, an uncommon reproductive pattern for tropical species. The correlation between flowering and lower precipitation supports possible insect pollination, though direct pollinator observations remain needed. The results concur with other studies indicating a correlation between fruit number and plant size. This investigation provides information on the reproductive phenology and fruit traits of P. turbinata, laying a foundation for future research into its interactions with pollinators and dispersers.